Embodied carbon mitigation and reduction in the built environment – What does the evidence say?. (1st October 2016) - Pomponi, Francesco; Moncaster, Alice
Abstract: Of all industrial sectors, the built environment puts the most pressure on the natural environment, and in spite of significant efforts the International Energy Agency suggests that buildings-related emissions are on track to double by 2050. Whilst operational energy efficiency continues to receive significant attention by researchers, a less well-researched area is the assessment of embodied carbon in the built environment in order to understand where the greatest opportunities for its mitigation and reduction lie. This article approaches the body of academic knowledge on strategies to tackle embodied carbon (EC) and uses a systematic review of the available evidence to answer the following research question: how should we mitigate and reduce EC in the built environment? 102 journal articles have been reviewed systematically in the fields of embodied carbon mitigation and reduction, and life cycle assessment. In total, 17 mitigation strategies have been identified from within the existing literature which have been discussed through a meta-analysis on available data. Results reveal that no single mitigation strategy alone seems able to tackle the problem; rather, a pluralistic approach is necessary. The use of materials with lower EC, better design, an increased reuse of EC-intensive materials, and stronger policy drivers all emerged as key elements for a quicker transition to a low carbon built environment. The meta-analysis on 77 LCAs also shows an extremely incomplete and short-sighted approach to life cycle studies. Most studies only assess the manufacturing stages, often completely overlooking impacts occurring during the occupancy stage and at the end of life of the building. The LCA research community have the responsibility to address such shortcomings and work towards more complete and meaningful assessments. Highlights: The article presents a systematic review on embodied carbon mitigation and reduction. Seventeen mitigation strategies have been identified and discussed. A meta-analysis informs on correlation, breadth and scope of the literature. The completeness of current LCA research is also analysed. The directions for future research efforts are suggested.